2016
DOI: 10.1614/ws-d-15-00087.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of apsbAMutation (Valine219to Isoleucine) in Powell Amaranth (Amaranthus powellii) Conferring Resistance to Linuron

Abstract: A Powell amaranth population suspected to be resistant (R) to linuron was discovered in a carrot field in Keswick, Ontario, Canada, in 1999. Dose–response analysis with different herbicides and DNA sequencing of thepsbAgene encoding the D1 protein of photosystem II were done to confirm the resistance and identify its basis. A calculated resistance factor indicated a 12-fold increased resistance when linuron was applied to an R population compared with a susceptible (S) population. Moreover, the R population sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
1
23
1
Order By: Relevance
“…In these cases, the mechanism that confers resistance to the herbicides of this group is Ser 264 Gly mutation in psbA gene, which changes the configuration of D1 protein of PS II, preventing the herbicides binding to the target binding site. In the case of simultaneous resistance to triazines and urea herbicides, the mechanisms most commonly found is Val 219 Ile mutation in the psbA gene (Mengistu et al, 2000(Mengistu et al, , 2005Dumont et al, 2016).…”
Section: Als Inhibitors (Trifloxysulfuron-sodium and Pyrithiobac-sodium)mentioning
confidence: 99%
“…In these cases, the mechanism that confers resistance to the herbicides of this group is Ser 264 Gly mutation in psbA gene, which changes the configuration of D1 protein of PS II, preventing the herbicides binding to the target binding site. In the case of simultaneous resistance to triazines and urea herbicides, the mechanisms most commonly found is Val 219 Ile mutation in the psbA gene (Mengistu et al, 2000(Mengistu et al, , 2005Dumont et al, 2016).…”
Section: Als Inhibitors (Trifloxysulfuron-sodium and Pyrithiobac-sodium)mentioning
confidence: 99%
“…The definition fails to note that the herbicide is the selective agent in the process leading to resistance. Instances of herbicide resistance date back to the 1950s, but the number of resistance cases has increased steadily since then (WSSA 2018 (Dumont et al 2016). In addition, resistant species have been found to have low level resistance to other PSII inhibitors such as atrazine, prometryn, metribuzin, bromoxynil and bentazon rendering these herbicides less effective (Dumont et al 2016).…”
Section: Linuron Resistant Pigweedmentioning
confidence: 99%
“…On a positive note, the resistance mutation occurs in the plastome meaning resistance cannot be passed on through pollen, but it will be spread by seed (Dumont et al 2016). Generally, a resistant weed species will appear as an isolated patch, but over only a few years that resistant population can dominate a field and the seedbank (WSSA 2018).…”
Section: Linuron Resistant Pigweedmentioning
confidence: 99%
“…Research with algae and cyanobacteria has shown that specific amino acid substitutions between positions Phe 211 and Leu 275 in the QB binding niche of the D1 protein confer resistance to PSII inhibitor herbicides . A summary of a number of studies with higher plants report eight substitutions in the D1 protein, Leu 218 Val, Val 219 Ile, Ala 251 Val, Phe 255 Ile, Phe 255 Val, Ser 264 Gly, Ser 264 Thr and Asn 266 Thr, as being associated with resistance to PSII inhibitors in various weed species . The type and extent of herbicide resistance depends upon the individual substitution and the species involved, with no one substitution providing resistance to all PSII inhibitors …”
Section: Introductionmentioning
confidence: 99%
“…6 A summary of a number of studies with higher plants report eight substitutions in the D1 protein, Leu 218 Val, Val 219 Ile, Ala 251 Val, Phe 255 Ile, Phe 255 Val, Ser 264 Gly, Ser 264 Thr and Asn 266 Thr, as being associated with resistance to PSII inhibitors in various weed species. 7 The type and extent of herbicide resistance depends upon the individual substitution and the species involved, with no one substitution providing resistance to all PSII inhibitors. 6 The only reported case of a crop species possessing a target site resistance to a PSII herbicide inhibitor is in canola (Brassica napus L.).…”
Section: Introductionmentioning
confidence: 99%